Antibiotic Resistance to Third Generation Cephalosporins Due to CTX-M-Type Extended-Spectrum β-Lactamases in Clinical Isolates of Escherichia coli - M Mirzaee; MR Pourmand; M Chitsaz; S Mansouri (Tehran University of Medical Sciences, 2009)
"nBackground: Organisms producing CTX-M-β-lactamase are emerging around the world as a source of resistance to oxyiminocephalosporins such as cefotaxime. However, the laboratory detection of these strains is not well defined. The aim of this study was to determine the presence and prevalence of known CTX-M-β-lactamases genes in clinical isolates of  Escherichia coli from hospitals of Tehran."nMethods: During six months (September to February, 2006), 160 clinical isolates of Escherichia coli collected from three university hospitals of Tehran.  Phenotypic screening and confirmation tests for ESBL detection was according to CLSI advised. All of the ESBL-producing isolates were examined by PCR for presence of bla CTX-M genes."nResults: Primary phenptypic tests revealed that %56.69 (n=89) of E. coli isolates produced ESBLs. In confirmatory tests by use of clavulanic acid, ESBL production were confirmed (P+C+) in %96.7 (n=86) of isolates with primary positive test. The presence of an ESBL was not confirmed (P+C-) in 3.3% (n=3) of the screen positive. Of all screen positive isolates, 34 (35.78%) were positive for bla CTX-M genes from the CTX-M-I group, indicating CTX-M-1-like β-lactamases and Two (2.1%) were positive for bla CTX-M genes from the CTX-M-III group, indicating CTX-M-3-like β-lactamases. The remainder 59 (62.2%) were negative for bla CTX-M genes."nConclusions: The levels of resistance to ceftazidim were remarkably varible among CTX-M producers. This study provides futher evidence of the global dissemination of  CTX-M type ESBLs and emphasize the need for their epidemiological monitoring.